Catalyst layer for fuel cell, method for producing same, membrane-electrode assembly, method for producing same, and fuel cell

JP7630009B2Active Publication Date: 2025-02-14KOLON INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023557765
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-07
Filing Date
2022-02-15
Publication Date
2025-02-14
Estimated Expiration
2042-02-15

AI Technical Summary

Benefits of technology

【0008】 本発明の一実施例にかかると、放熱素材の優れた熱伝導性により膜-電極アセンブリの内部で発生する熱を効率的に放出する燃料電池用触媒層を提供することができる。 本発明の別の実施例にかかると、放熱素材を燃料電池用触媒層に適用することによって、高温または低加湿の条件で燃料電池の性能が低下するという問題点を解決する燃料電池用触媒層を提供することができる。 本発明のまた別の実施例にかかると、放熱素材及び第2アイオノマーを含む第2複合体を高分子電解質膜及び触媒層の界面にランダム(Random)に配置させることによって、高分子電解質膜と触媒層との結合力を向上させて機械的耐久性が改善された燃料電池用触媒層を提供することができる。 本発明の一実施例にかかると、前記デカール方法の問題点を解決するために、第1アイオノマー溶液と触媒が分散された水溶液とを混合し、これを分散、乾燥及び再分散するステップを介して第1均質混合物を製造するステップと、放熱素材と第2アイオノマー溶液とを混合して放熱素材を含む第2均質混合物を製造するステップを別途行い、前記第2均質混合物を前記第1均質混合物と混合することによって、高分子電解質膜に直接コーディングされるコーディング組成物を製造する燃料電池用触媒層の製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630009000002
    Figure 0007630009000002
  • Figure 0007630009000003
    Figure 0007630009000003
  • Figure 0007630009000004
    Figure 0007630009000004
Patent Text Reader

Abstract

A catalyst layer for a fuel cell having improved heat dissipation performance and durability is provided. The catalyst layer for a fuel cell according to the present invention is a catalyst layer for a fuel cell comprising a first composite and a second composite, the first composite comprising a support, a catalyst comprising metal particles supported on the support, and a first ionomer coated on a surface of the catalyst, the second composite comprising a heat dissipation material and a second ionomer, the second ionomer not being coated on the surface of the catalyst, and the first ionomer and the second ionomer being the same or different from each other.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst layer for a fuel cell, a manufacturing method thereof, a membrane-electrode assembly, a manufacturing method thereof, and a fuel cell, and more particularly, to a catalyst layer for a fuel cell, a manufacturing method thereof, a membrane-electrode assembly, a manufacturing method thereof, and a fuel cell, which not only efficiently release heat generated inside the membrane-electrode assembly due to the excellent thermal conductivity of a heat dissipation material, but also prevent a decrease in humidity due to high temperatures, and which increase the binding strength between a polymer electrolyte membrane and a catalyst layer by using a second composite, thereby improving the durability of the membrane-electrode assembly. [Background technology]

[0002] Fuel cells are batteries equipped with a power generation system that directly converts chemical reaction energy, such as the oxidation / reduction reaction of hydrogen and oxygen contained in hydrocarbon fuel substances such as methanol, ethanol, and natural gas, into electrical energy. Due to their high energy efficiency and environmentally friendly characteristics of low pollutant emissions, fuel cells have been attracting attention as a next-generation clean energy source to replace fossil energy. Such fuel cells have the advantage of being able to produce a wide range of output power due to their stack configuration made up of layered unit cells, and because they exhibit an energy density 4 to 10 times that of small lithium batteries, they are attracting attention as small and portable power sources for mobile use. The stack that actually generates electricity in a fuel cell has a structure in which several to several tens of unit cells, each of which is made up of a membrane-electrode assembly (MEA) and a separator (also called a bipolar plate), are stacked. The membrane-electrode assembly generally has a structure in which an anode (or fuel electrode) and a cathode (or air electrode) are formed on either side of an electrolyte membrane.

[0003] Fuel cells can be classified into alkaline electrolyte membrane fuel cells, polymer electrolyte membrane fuel cells (PEMFC), etc. depending on the state and type of electrolyte. Among them, polymer electrolyte membrane fuel cells are attracting attention as portable, vehicular and home power sources due to their advantages such as low operating temperature of less than 100℃, fast start-up and response characteristics, and excellent durability. Representative examples of polymer electrolyte membrane fuel cells include the Proton Exchange Membrane Fuel Cell (PEMFC), which uses hydrogen gas as fuel, and the Direct Methanol Fuel Cell (DMFC), which uses liquid methanol as fuel. To summarize the reactions that occur in a polymer electrolyte membrane fuel cell, first, when a fuel such as hydrogen gas is supplied to the anode electrode, the hydrogen gas is oxidized at the anode electrode to produce hydrogen ions (H + ) and electrons (e - The hydrogen ions are transferred to the cathode electrode via the polymer electrolyte membrane, and the electrons are transferred to the cathode electrode via an external circuit. Oxygen gas is supplied to the cathode electrode, and the oxygen combines with the hydrogen ions and electrons to produce water through a reduction reaction of oxygen. On the other hand, there are still many technical barriers to be overcome in order to commercialize polymer electrolyte membrane fuel cells, and essential improvements include realizing high performance, long life, and low cost. The component that has the greatest impact on this is the membrane-electrode assembly.

[0004] Conventional membrane-electrode assemblies have a tendency to have difficulty in normally exhibiting high performance in a specific temperature and relative humidity environment, especially in a high temperature or low humidity condition, which limits the range of use of polymer electrolyte membrane fuel cells to which conventional membrane-electrode assemblies are applied. Therefore, research is being continuously conducted to solve the problem of reduced humidity due to high temperatures in polymer electrolyte membrane fuel cells and to achieve high mechanical strength. Meanwhile, the decal method, in which a coating composition is first applied onto another support (or decal film) such as Teflon and then the resulting catalyst layer is transferred to a polymer electrolyte membrane, has problems in that the ionomer-rich region rises to the top, hindering the transfer of materials, and the relatively ionomer-poor region is disposed toward the polymer electrolyte membrane, reducing the interfacial adhesion. In order to solve these problems, research is being continuously conducted into a direct coating technology in which a coating composition is directly coated onto a polymer electrolyte membrane. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present invention is to provide a catalyst layer for a fuel cell that efficiently dissipates heat generated inside a membrane-electrode assembly by utilizing the excellent thermal conductivity of a heat dissipation material. Another object of the present invention is to provide a catalyst layer for a fuel cell that solves the problem of the performance of the fuel cell decreasing under high temperature or low humidity conditions by applying a heat dissipation material to the catalyst layer for the fuel cell. Another object of the present invention is to provide a catalyst layer for a fuel cell having improved mechanical durability by randomly disposing a second composite including a heat dissipation material and a second ionomer at the interface between a polymer electrolyte membrane and a catalyst layer, thereby improving the bonding strength between the polymer electrolyte membrane and the catalyst layer. Another object of the present invention is to provide a method for manufacturing a catalyst layer for a fuel cell, which solves the problems of the decal method by separately carrying out a step of preparing a first homogeneous mixture by mixing a first ionomer solution with an aqueous solution in which a catalyst is dispersed, and then dispersing, drying, and redispersing the mixture, and a step of preparing a second homogeneous mixture containing a heat dissipating material by mixing a heat dissipating material with a second ionomer solution, and mixing the second homogeneous mixture with the first homogeneous mixture to prepare a coating composition that can be directly coated on a polymer electrolyte membrane.

[0006] Another object of the present invention is to provide a membrane-electrode assembly including the above-mentioned catalyst layer for a fuel cell. Another object of the present invention is to provide a method for manufacturing a membrane-electrode assembly, in which the coating composition is directly coated on the polymer electrolyte membrane, and then the coated polymer electrolyte membrane is dried, thereby precipitating a second complex uniformly distributed in the coating composition at the interface between the polymer electrolyte membrane and a catalyst layer, thereby improving the bonding strength at the interface. Another object of the present invention is to provide a fuel cell comprising said membrane-electrode assembly. The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and will be more clearly understood by the embodiments of the present invention. In addition, it is easily understood that the object and advantages of the present invention can be realized by the means and combinations thereof shown in the claims. [Means for solving the problem]

[0007] To achieve the above object, one embodiment of the present invention provides a catalyst layer for a fuel cell comprising a first composite and a second composite, the first composite comprising a support, a catalyst comprising metal particles supported on the support, and a first ionomer coated on a surface of the catalyst, the second composite comprising a heat dissipation material and a second ionomer, the second ionomer being not coated on the surface of the catalyst, and the first ionomer and the second ionomer being the same or different from each other. In another embodiment of the present invention to achieve the above object, there is provided a method for manufacturing a catalyst layer for a fuel cell, comprising the steps of: (S1) homogeneously mixing a first ionomer solution with an aqueous solution having a catalyst dispersed therein, and dispersing the mixture to prepare a first homogeneous mixture; and (S2) adding a second homogeneous mixture, in which a heat dissipating material and a second ionomer solution are mixed, to the first homogeneous mixture, and dispersing the mixture to prepare a coating composition. In accordance with another embodiment of the present invention to achieve the above object, there is provided a membrane-electrode assembly including a polymer electrolyte membrane and a catalyst layer for a fuel cell disposed on at least one surface of the polymer electrolyte membrane. In another embodiment of the present invention to achieve the above object, a method for manufacturing a membrane-electrode assembly may be provided, comprising the steps of directly coating a coating composition on at least one surface of a polymer electrolyte membrane, and drying the polymer electrolyte membrane coated with the coating composition, wherein the method for manufacturing the coating composition comprises the steps of (S1) homogeneously mixing a first ionomer solution and an aqueous solution having a catalyst dispersed therein, and dispersing them to prepare a first homogeneous mixture, and (S2) adding a second homogeneous mixture, in which a heat dissipating material and a second ionomer solution are mixed, to the first homogeneous mixture, and dispersing them. To achieve the above object, another embodiment of the present invention provides a fuel cell including the above membrane-electrode assembly. Effect of the Invention

[0008] According to an embodiment of the present invention, a catalyst layer for a fuel cell can be provided that efficiently dissipates heat generated inside a membrane-electrode assembly due to the excellent thermal conductivity of a heat dissipation material. According to another embodiment of the present invention, by applying a heat dissipation material to a catalyst layer for a fuel cell, a catalyst layer for a fuel cell can be provided that solves the problem of the performance of the fuel cell decreasing under high temperature or low humidity conditions. According to another embodiment of the present invention, a second composite including a heat dissipation material and a second ionomer is randomly disposed at the interface between a polymer electrolyte membrane and a catalyst layer, thereby improving the bonding strength between the polymer electrolyte membrane and the catalyst layer, thereby providing a catalyst layer for a fuel cell having improved mechanical durability. According to one embodiment of the present invention, in order to solve the problems of the decal method, a method for manufacturing a catalyst layer for a fuel cell can be provided, which comprises the steps of preparing a first homogeneous mixture by mixing a first ionomer solution with an aqueous solution having a dispersed catalyst, dispersing, drying, and redispersing the mixture, and preparing a second homogeneous mixture containing a heat dissipating material by mixing a heat dissipating material with a second ionomer solution, and mixing the second homogeneous mixture with the first homogeneous mixture to prepare a coating composition that is directly coated on a polymer electrolyte membrane.

[0009] According to one embodiment of the present invention, there is provided a method for manufacturing a membrane-electrode assembly, in which the coating composition is directly coated onto a polymer electrolyte membrane, and then the coated polymer electrolyte membrane is dried, thereby precipitating a second complex uniformly distributed within the coating composition at the interface between the polymer electrolyte membrane and a catalyst layer, thereby improving the bonding strength between the interfaces. In addition to the above-mentioned advantages, specific advantages of the present invention will be described below while explaining specific details for carrying out the invention. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing a fuel cell catalyst layer according to an embodiment of the present invention. [Diagram 2]2 is a flow chart showing a method for manufacturing a fuel cell catalyst layer according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a cross-sectional view showing a membrane-electrode assembly according to one embodiment of the present invention. [Figure 4] FIG. 1 is a schematic diagram illustrating how a second complex homogeneously dispersed in a coating composition precipitates at the interface between a polymer electrolyte membrane and a catalyst layer in a manufacturing method of a membrane-electrode assembly according to one embodiment of the present invention. [Diagram 5] FIG. 1 is a schematic diagram for explaining a fuel cell according to an embodiment of the present invention. [Figure 6] 1 is a transmission electron microscope (TEM) photograph of an electrode of a membrane-electrode assembly according to Example 1. [Figure 7] 1 is a transmission electron microscope (TEM) photograph of a second composite body according to Example 3. [Figure 8] 1 is a scanning electron microscope (SEM) photograph of an electrode of a membrane-electrode assembly according to Example 4. [Figure 9] This is a scanning electron microscope (SEM) photograph of an electrode when h-BN (hexagonal boron nitride) is 52 wt % based on the total weight of the second homogeneous mixture. [Figure 10] 1 is a scanning electron microscope (SEM) photograph showing second complexes randomly distributed at the interface (or first segment) between a fuel cell catalyst layer and a polymer electrolyte membrane according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, each component of the present invention will be described in more detail so that a person having ordinary skill in the art to which the present invention pertains can easily implement the present invention. However, this is merely an example, and the scope of the present invention is not limited to the following content. One embodiment of the present invention provides a catalyst layer for a fuel cell comprising a first composite and a second composite, the first composite comprising a support, a catalyst comprising metal particles supported on the support, and a first ionomer coated on a surface of the catalyst, the second composite comprising a heat dissipation material and a second ionomer, the second ionomer not being coated on a surface of the catalyst, and the first ionomer and the second ionomer being the same or different from each other.

[0012] The configuration of the present invention will be described in more detail below with reference to the drawings. 1 is a cross-sectional view showing a fuel cell catalyst layer according to an embodiment of the present invention. For convenience of explanation, a polymer electrolyte membrane 10 and first to fourth segments 20, 20', 30 and 30' will be described later with reference to FIG. The fuel cell catalyst layer 25 according to the present invention may include a first composite body 18 and a second composite body 28 . The first composite 18 may include a support 12 , a catalyst 16 including metal particles supported on the support 12 , and a first ionomer 14 coated on a surface of the catalyst 16 . The support 12 according to the present invention is one which facilitates electron exchange with the catalyst, and may be one selected from the group consisting of carbon-based supports, porous inorganic oxides, zeolites, and combinations thereof.

[0013] The carbon-based support may be selected from graphite, Super P, carbon fiber, carbon sheet, carbon black, Ketjen black, Denka black, acetylene black, carbon nanotube (CNT), carbon sphere, carbon ribbon, fullerene, activated carbon, carbon nanofiber, carbon nanowire, carbon nanoball, carbon nanohorn, carbon nanocage, carbon nanoring, ordered nano- / meso-porous carbon, carbon aerogel, mesoporous carbon, graphene, stabilized carbon, activated carbon, and at least one combination thereof, but is not limited thereto, and any support available in the art may be used without limitation.

[0014] The porous inorganic oxide may be at least one selected from the group consisting of zirconia, alumina, titania, silica, and ceria. The surface area of ​​the carrier 12 is 50 m 2 / g or more, and the average particle size is preferably 10 to 300 nm (nanometers). If the surface area of ​​the support is less than the above range, uniform distribution of the metal particles cannot be obtained. The catalyst 16 containing metal particles according to the present invention may be any catalyst that can be used in a hydrogen gas oxidation reaction and / or an oxygen gas reduction reaction. The metal particles according to the present invention may be one selected from the group consisting of platinum-based metals, platinum-based alloys, non-platinum-based metals, and non-platinum-based alloys. The metal particles may be disposed on the surface of the support 12, or may permeate the inside of the support 12 while filling the internal pores of the support 12. The platinum-based metal may be platinum (Pt) and / or a Pt-M alloy, where M may be any one or more selected from the group consisting of palladium (Pd), ruthenium (Ru), iridium (Ir), osmium (Os), gallium (Ga), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), silver (Ag), gold (Au), zinc (Zn), tin (Sn), molybdenum (Mo), tungsten (W), lanthanum (La), and rhodium (Rh). Specifically, the platinum-based alloy (Pt-M) may be Pt-Pd, Pt-Sn, Pt-Mo, Pt-Cr, Pt-W, Pt-Ru, Pt-Ni, Pt-Ru-W, Pt-Ru-Ni, Pt-Ru-Mo, Pt-Ru-Rh-Ni, Pt-Ru-Sn-W, Pt-Ru-Ir-Ni, Pt-Co, Pt-Co-Mn, Pt-Co-Ni, Pt-Co-Fe, Pt-Co-Ir, Pt-Co-S, Pt-Co-P, Pt-Fe, Pt-Fe-Ir, Pt-Fe-S, Pt-Fe-P, Pt-Au-Co, Pt-Au-Fe, Pt-Au-Ni, Pt-Ni, Pt-Ni-Ir, Pt-Cr, Pt-Cr-Ir, or a mixture of two or more of these.

[0015] The non-platinum metal may be at least one selected from the group consisting of palladium (Pd), ruthenium (Ru), iridium (Ir), osmium (Os), and non-platinum alloys. The non-platinum alloy may be Ir-Fe, Ir-Ru, Ir-Os, Co-Fe, Co-Ru, Co-Os, Rh-Fe, Rh-Ru, Rh-Os, Ir-Ru-Fe, Ir-Ru-Os, Rh-Ru-Fe, Rh-Ru-Os, Fe-N, Fe-P, Co-N, or a mixture of two or more of these. The first ionomer 14 according to the present invention may be coated on the surface of the catalyst 16 including the metal particles. The first ionomer 14 may also be coated on the surface of the support 12. The first ionomer 14 may be one selected from the group consisting of fluorine-based ionomers, hydrocarbon-based ionomers, and mixtures thereof.

[0016] The fluorine-based ionomer may be a fluorine-containing polymer having a cation exchange group or an anion exchange group and containing fluorine in the main chain, or a partially fluorinated polymer such as polystyrene-graft-ethylene tetrafluoroethylene copolymer, polystyrene-graft-polytetrafluoroethylene copolymer, etc. The fluorine-based ionomer may be a fluorine-containing polymer including, for example, poly(perfluorosulfonic acid), poly(perfluorocarboxylic acid), copolymer of tetrafluoroethylene and fluorovinyl ether containing sulfonic acid groups, and defluorinated sulfurized polyether ketone, or a mixture thereof. The cation exchange group is a functional group capable of transferring cations such as hydrogen ions, and may be, for example, an acidic group such as a sulfonic acid group, a carboxyl group, a boronic acid group, a phosphate group, an imide group, a sulfonimide group, or a sulfonamide group, and generally may be a sulfonic acid group or a carboxyl group. The anion exchange group is a polymer capable of transporting anions such as hydroxide ions, carbonates, or bicarbonates. The anion exchange group is commercially available in the form of hydroxide or halide (generally chloride). The anion exchange group may be used in industrial water purification, metal separation, or catalytic processes, etc. As the polymer containing the anion exchange group, a polymer doped with a metal hydroxide may generally be used. Specifically, a metal hydroxide-doped poly(ether sulfone), polystyrene, vinyl polymer, poly(vinyl chloride), poly(vinylidene fluoride), poly(tetrafluoroethylene), poly(benzimidazole), or poly(ethylene glycol) may be used.

[0017] The hydrocarbon ionomer may be a hydrocarbon polymer having a cation exchange group or an anion exchange group. For example, the hydrocarbon polymer may be a hydrocarbon polymer having at least one selected from the group consisting of imidazole, benzimidazole, polyamide, polyamideimide, polyimide, polyacetal, polyethylene, polypropylene, acrylic resin, polyester, polysulfone, polyether, polyetherimide, polyester, polyethersulfone, polyetherimide, polycarbonate, polystyrene, polyphenylene sulfide, polyetheretherketone, polyetherketone, polyarylethersulfone, polyphosphazene, and polyphenylquinoxaline in the main chain.

[0018] The hydrocarbon ionomer may be a sulfonated polyimide (S-PI), a sulfonated polyarylethersulfone (S-PAES), a sulfonated polyetheretherketone (S-PEEK), a sulfonated polybenzimidazole (S-PBI), a sulfonated polysulfone (S-PSU), a sulfonated polystyrene (S-PS), a sulfonated polyphosphazene, a sulfonated polyquinoxaline, a sulfonated polyketone, a sulfonated polyphenylene oxide, a sulfonated polyethersulfone ... sulfone, sulfonated polyether ketone, sulfonated polyphenylene sulfone, sulfonated polyphenylene sulfide, sulfonated polyphenylene sulfide sulfone, sulfonated polyphenylene sulfide sulfone nitrile, sulfonated polyarylene ether, sulfonated polyarylene ether nitrilenitrile, sulfonated polyarylene ether ether nitrile, sulfonated polyarylene ether sulfone ketone, and hydrocarbon polymers including mixtures thereof, but the technical idea of ​​the present invention is not limited thereto.

[0019] A second composite 28 according to the present invention may include a heat interface material 26 and a second ionomer 24 . The heat dissipation material 26 may be one selected from the group consisting of metal nanoparticles, ceramic nanoparticles, ultra-high molecular weight polyethylene, polyacetylene, polyimide, carbon-based nanoparticles, and combinations thereof. The metal nanoparticles may be one selected from the group consisting of Al, Mg, Cu, Ni, Ag, and core-shell structured metal particles, each of which has excellent thermal conductivity. The size of the metal nanoparticles is preferably 5 to 30 nm (nanometers). As used herein, a core-shell structure is defined as one in which a shell (or skin) forming material surrounds a core (or central) material. Specifically, the core-shell structured metal particles of the present invention can serve as a heat dissipation material with excellent thermal conductivity, while forming a chemical and mechanical protective layer for the core material through the shell portion and maintaining the inherent properties of each of the core and shell constituent materials.

[0020] In the core-shell metal particles, the core may be a metal or metalloid belonging to Groups 2 to 15 of the periodic table, and the shell may be a metal having excellent thermal conductivity or being relatively stable, such as Cu@Ag, Fe@Al, or Cu@Au. By forming the inorganic oxide or metal oxide as a shell, the metal particles having the core-shell structure can efficiently release heat generated inside the membrane-electrode assembly during operation of the fuel cell. The ceramic nanoparticles may be one or more selected from the group consisting of boron nitride, aluminum nitride, aluminum oxide, silicon carbide, and beryllium oxide. In particular, among the boron nitrides, hexagonal boron nitride (h-BN) has similar physical properties and a plate-like structure to graphite compared to ordinary boron nitride, and has excellent thermal conductivity, insulation properties, and chemical stability at high temperatures. The ceramic nanoparticles have excellent thermal conductivity, and can easily transfer heat to the outside of the catalyst layer, and can prevent moisture in the catalyst layer from evaporating. The average diameter of the ceramic nanoparticles is preferably 10 to 500 nm (nanometers), and more preferably 30 to 300 nm (nanometers).

[0021] If the average diameter of the ceramic nanoparticles is larger than the above range, the increase in surface area due to the large particles is negligible, which may result in a problem in that it is difficult to provide a proper heat dissipation effect. If the average diameter is smaller than the above range, a problem may occur in which the particles clump together or around the catalyst, which may actually reduce the function of the catalyst. The weight average molecular weight (Mw) of the ultrahigh molecular weight polyethylene may be 3,500,000 to 10,500,000 g / mol. If the weight average molecular weight of the ultrahigh molecular weight polyethylene is below this range, the efficiency of heat dissipation of the fuel cell catalyst layer may be reduced. The polyacetylene has a conjugation structure, which is a molecular structure in which single and double bonds between carbon and carbon are alternately shown, and therefore the pi electrons of the polyacetylene are not distributed unevenly throughout the entire molecular structure, so that the polyacetylene can have excellent electrical conductivity and heat dissipation effects. When the weight average molecular weight (Mw) of the polyacetylene is 20,000 to 1,000,000 g / mol, the polyacetylene can efficiently release heat inside the catalyst layer due to its long chain structure, but the technical idea of ​​the present invention is not limited to the weight average molecular weight of the polyacetylene.

[0022] Polyimide is known as a polymer that has excellent heat dissipation performance, mechanical strength, and chemical resistance, and can be used as the heat dissipation material. The carbon-based nanoparticles may be selected from the group consisting of carbon nanofiber, carbon black, acetylene black, carbon nanotube (CNT), carbon sphere, carbon ribbon, fullerene, graphene, activated carbon, and combinations of one or more thereof, but are not limited thereto. In particular, when the carbon-based nanoparticles are mixed with a metal, the heat dissipation effect may be more pronounced, and the heat generated in the membrane-electrode assembly to which the fuel cell catalyst layer 25 is applied may be effectively dissipated. Similarly, when the ultra-high molecular weight polyethylene is mixed with a metal, the heat dissipation effect may be more pronounced, and the heat generated in the membrane-electrode assembly to which the fuel cell catalyst layer 25 is applied may be effectively dissipated. The second ionomer 24 of the present invention may not be coated on the surface of the catalyst 16. In other words, the second ionomer 24 may include the heat dissipating material 26, and the heat dissipating material 26 may be dispersed within the second ionomer 24. In other words, the second ionomer 24 may surround the heat dissipating material 26. The first ionomer 14 and the second ionomer 24 according to the present invention may be the same or different from each other. Thus, the material of the first ionomer 14 and the material of the second ionomer 24 may be the same or different from each other.

[0023] Furthermore, the equivalent weight of the first ionomer 14 and the equivalent weight of the second ionomer 24 are each independently 600 to 1100 g / eq, and the equivalent weight of the first ionomer 14 and the equivalent weight of the second ionomer 24 may be different from each other. According to an embodiment of the present invention, one of the first ionomer 14 and the second ionomer 24 may be a fluorine-based ionomer, and the other may be a hydrocarbon-based ionomer. According to another embodiment of the present invention, the first ionomer 14 may be a first hydrocarbon-based ionomer, and the second ionomer 24 may be a second hydrocarbon-based ionomer different from the first hydrocarbon-based ionomer. According to another embodiment of the present invention, the first ionomer 14 may be a first fluorine-based ionomer, and the second ionomer 24 may be a second fluorine-based ionomer different from the first fluorine-based ionomer. The fuel cell catalyst layer 25 according to an embodiment of the present invention may further include a functional additive.

[0024] The functional additive may be at least one selected from the group consisting of a radical scavenger, a gas barrier particle, a hydrophilic inorganic additive, an oxygen evolution reaction (OER) catalyst, and combinations thereof. The radical scavenger may include at least one selected from the group consisting of a metal-based peroxide decomposition accelerator, an organic peroxide decomposition accelerator, and a peroxide decomposition accelerator salt compound. The metal-based peroxide decomposition accelerator may include at least one selected from the group consisting of cerium ions, nickel ions, tungsten ions, cobalt ions, chromium ions, zirconium ions, yttrium ions, manganese ions, iron ions, titanium ions, vanadium ions, molybdenum ions, lanthanum ions, neodymium ions, silver ions, platinum ions, ruthenium ions, palladium ions, and rhodium ions. The metal-based peroxide decomposition accelerator may include an oxide of a metal or a precious metal, and the oxide of a metal or a precious metal may include at least one selected from the group consisting of cerium oxide, nickel oxide, tungsten oxide, cobalt oxide, chromium oxide, zirconium oxide, yttrium oxide, manganese oxide, iron oxide, titanium oxide, vanadium oxide, molybdenum oxide, lanthanum oxide, and neodymium oxide. The organic peroxide decomposition accelerator may be at least one selected from the group consisting of syringic acid, vanillic acid, protocatechuic acid, coumaric acid, caffeic acid, ferulic acid, chlorogenic acid, cynarine, gallic acid, and mixtures thereof.

[0025] The peroxide decomposition-accelerating salt compound may include a salt of a metal including a transition metal or a noble metal, which may be any one selected from the group consisting of carbonates, acetates, chlorides, fluorides, sulfates, phosphates, tungstates, hydroxides, ammonium acetates, ammonium sulfates, acetylacetonates, and permanganates of the metals, and specifically includes cerium such as cerium carbonate, cerium acetate, cerium chloride, cerium acetate, cerium sulfate, ammonium cerium acetate, and ammonium cerium sulfate, and an organic metal complex such as cerium acetylacetonate. The gas barrier particles may be any one selected from the group consisting of clay, montmorillonite, saponite, laponite, mica, fluorohectorite, kaolinite, vermiculite, and combinations thereof. The hydrophilic inorganic additive may be at least one selected from the group consisting of SnO2, silica, alumina, zirconia, mica, zeolite, phosphongstic acid, silicon tungstic acid, zirconium hydrogen phosphate, and combinations thereof. The hydrophilic inorganic additive may prevent a decrease in hydrogen ion conductivity under high temperature and low humidity conditions.

[0026] The oxygen generation reaction catalyst is finely or uniformly dispersed in the fuel cell catalyst layer, and can improve the durability of the fuel cell catalyst layer through an effective water splitting reaction. The oxygen generation reaction catalyst may include the above-mentioned platinum-based metal and / or non-platinum-based metal active material. Hereinafter, the description of the platinum-based metal or non-platinum-based metal active material that overlaps with the above description will be omitted. Another embodiment of the present invention corresponds to a method for manufacturing a catalyst layer for a fuel cell, comprising the steps of: (S1) homogeneously mixing a first ionomer solution with an aqueous solution having a catalyst dispersed therein, and dispersing the mixture to prepare a first homogeneous mixture; and (S2) adding a second homogeneous mixture, in which a heat dissipating material and a second ionomer solution are mixed, to the first homogeneous mixture, and dispersing the mixture to prepare a coating composition. In the step (S1), a method for primarily dispersing the homogeneously mixed mixture of the first ionomer solution and the aqueous solution having the catalyst dispersed therein may be one selected from the group consisting of a homogeneous mixer, a high-pressure disperser, a ball mill, a powder mixer, and a resonant acoustic mixer. The method for producing a fuel cell catalyst layer according to another embodiment of the present invention may further include a step of drying the first homogeneous mixture at 80 to 120° C. for 8 to 10 hours between the steps (S1) and (S2).

[0027] The method for manufacturing a catalyst layer for a fuel cell may further include a step of heat-treating the dried first homogeneous mixture for 2 to 4 hours at 100 to 120° C. If the dried first homogeneous mixture is heat-treated outside the above range, the ionomer may form a strong bond with the surface of the catalyst, resulting in a decrease in catalyst activity or insufficient bonding strength between the catalyst and the ionomer. The method for manufacturing a fuel cell catalyst layer may include the step of redispersing the heat-treated first homogeneous mixture to prepare a first composite. The heat dissipating material according to the present invention may be included in an amount of 1 to 51 wt %, preferably 5 to 40 wt %, based on the total weight of the second homogeneous mixture. In other words, the heat dissipating material may be included in an amount of 5 to 25 wt %, preferably 6 to 20 wt %, based on the total solid weight of the coating composition. If the content of the heat dissipating material is less than the above range, the heat generated in the membrane-electrode assembly may not be effectively released, and if the content exceeds the above range, the heat dissipating material may clump and be difficult to disperse in the second ionomer solution, and the second ionomer may not function as a free ionomer, so that the binding strength between the polymer electrolyte membrane and the catalyst layer may not be improved. As a result, the durability of the membrane-electrode assembly may not be improved.

[0028] 2 is a flow chart showing a method for manufacturing a fuel cell catalyst layer according to one embodiment of the present invention. Descriptions that are repeated above will be simplified or omitted. Referring to FIG. 2, a method for manufacturing a catalyst layer for a fuel cell according to an embodiment of the present invention may include the steps of: homogenously mixing a first ionomer solution and an aqueous solution having a dispersed catalyst and dispersing them to prepare a first homogenous mixture (S10); drying the first homogenous mixture at 80-120° C. for 8-10 hours and heat-treating the dried first homogenous mixture at 100-120° C. for 2-4 hours (S20); mixing a heat dissipating material and a second ionomer solution to prepare a second homogenous mixture (S30); adding the second homogenous mixture to the first homogenous mixture and dispersing them (S40); and preparing a coating composition (S50). According to an embodiment of the present invention, the step (S20) may include a step of redispersing the heat-treated first homogeneous mixture to prepare a first composite. Yet another embodiment of the present invention relates to a membrane-electrode assembly including a polymer electrolyte membrane and a catalyst layer for a fuel cell disposed on at least one surface of the polymer electrolyte membrane.

[0029] 3 is a cross-sectional view showing a membrane-electrode assembly according to an embodiment of the present invention. The repeated explanations of the above-mentioned parts will be simplified or omitted. 3, in this specification, a first direction D1 may be defined as a thickness direction of a film, and a second direction D2 may be defined as a direction intersecting the first direction D1. For example, the second direction D2 may correspond to a direction perpendicular to the first direction D1. The polymer electrolyte membrane 10 according to the present invention may include an ion conductor. The ion conductor may be one selected from the group consisting of a fluorine-based ionomer, a hydrocarbon-based ionomer, and a mixture thereof. The ion conductor may have the same or different structure as the first ionomer described above. The description will not be repeated. The polymer electrolyte membrane 10 according to the present invention may be in the form of a reinforced composite membrane in which the pores of a porous support, such as a fluorine-based porous support such as e-PTFE having a microstructure of polymer fibrils or a microstructure in which nodes are interconnected by fibrils, or a porous nanoweb support manufactured by electrospinning or the like, are filled with an ion conductor.

[0030] The thickness of the polymer electrolyte membrane 10 may be 3 to 100 μm (micrometers), and preferably 5 to 20 μm (micrometers). However, the technical concept of the present invention is not limited to the thickness of the polymer electrolyte membrane. 1 and 3, the second composite 28 according to the present invention may be irregularly or randomly arranged in contact with a portion of the polymer electrolyte membrane 10. When the second composite 28 contacts a portion of the polymer electrolyte membrane 10, an ionomer-rich layer rich in the second ionomer may be formed, and the bonding strength between the polymer electrolyte membrane 10 and the fuel cell catalyst layer 25 may be increased, thereby improving the durability of the membrane-electrode assembly. 1 and 3, a portion of the fuel cell catalyst layer 25 according to the present invention is disposed on one surface of the polymer electrolyte membrane 10 and may include a first segment 20 and a second segment 30. Another part of the fuel cell catalyst layer 25 according to the present invention is disposed on the other side opposite to the one side of the polymer electrolyte membrane 10 and may include a third segment 20' and a fourth segment 30'. In this specification, the term "segment" is defined to include a part or region, and more broadly, a layer. The first and second segments 20 and 30 may function as an anode that receives hydrogen gas and generates hydrogen ions and electrons, while the third and fourth segments 20' and 30' may function as a cathode that receives the hydrogen ions and the electrons via the polymer electrolyte membrane 10 and an external circuit (not shown) and reduces oxygen gas supplied from the outside to generate water. The first segment 20 according to an embodiment of the present invention may be in contact with the polymer electrolyte membrane 10. In other words, it means that no member is interposed between the polymer electrolyte membrane 10 and the first segment 20. The third segment 20′ may also be in contact with the polymer electrolyte membrane 10, similar to the first segment 20.

[0031] According to an embodiment of the present invention, the second segment 30 may be disposed on the first segment 20. Specifically, the second segment 30 may be disposed directly on the first segment 20, or may be integrally formed with the first segment 20. In this specification, the meaning of "one member is disposed directly on another member" is defined as no member being interposed between the one member and the other member. Similarly, the fourth segment 30' may be disposed on the third segment 20', or specifically, may be disposed directly on the third segment 20'. 1 and 3, the second segment 30 according to an embodiment of the present invention may not include the second complex 28, or the content of the second complex 28 per unit volume of the second segment 30 may be less than the content of the second complex 28 per unit volume of the first segment 20. Similarly, the fourth segment 30' according to an embodiment of the present invention may not include the second complex 28, or the content of the second complex 28 per unit volume of the fourth segment 30' may be less than the content of the second complex 28 per unit volume of the third segment 20'. This is because, after the coating composition is directly coated onto one side of the polymer electrolyte membrane 10, when the coated polymer electrolyte membrane 10 is dried, the second composite 28 precipitates onto the polymer electrolyte membrane 10. Meanwhile, the thickness of the first segment 20 may be 10 to 800 nm (nanometers), and preferably 30 to 500 nm (nanometers). If the thickness of the first segment 20 is less than the above numerical range, the effect of strengthening the interfacial bonding force may not be exhibited, and if it exceeds the above numerical range, the amount of ionomer increases, which may cause a problem of impeding the transfer of material. The thickness of the third segment 20' may be in the above numerical range, similar to the thickness of the first segment 20.

[0032] The thickness of the second segment 30 may be 0.5 to 20 μm (micrometers), and preferably 1 to 15 μm (micrometers). If the thickness of the second segment 30 is less than the above numerical range, the electrode loading amount may be low and activity may be reduced, and if the thickness exceeds the above numerical range, material transfer may not be smooth, resistance may increase, and performance may be reduced. The thickness of the fourth segment 30′ may be in the above numerical range, similar to the thickness of the second segment 30. Referring to FIG. 3, the membrane-electrode assembly 100 according to the present invention may further include a first gas diffusion layer 40 and a second gas diffusion layer 40'. The first gas diffusion layer 40 according to the present invention may be disposed on a portion of the fuel cell catalyst layer 25. The first gas diffusion layer 40 may face the polymer electrolyte membrane 10 with the portion of the fuel cell catalyst layer 25 interposed therebetween. In other words, the portion of the fuel cell catalyst layer 25 may be disposed between the first gas diffusion layer 40 and the polymer electrolyte membrane 10. Furthermore, the first gas diffusion layer 40 may be disposed so as to face the first segment 20 with the second segment 30 interposed therebetween. The second gas diffusion layer 40' according to the present invention may be disposed on a part of the fuel cell catalyst layer 25 that is different from the part. The second gas diffusion layer 40' may face the polymer electrolyte membrane 10 with the other part of the fuel cell catalyst layer 25 interposed therebetween. In other words, the other part of the fuel cell catalyst layer 25 may be disposed between the second gas diffusion layer 40' and the polymer electrolyte membrane 10. Furthermore, the second gas diffusion layer 40' may be disposed so as to face the third segment 20' with the fourth segment 30' interposed therebetween. A porous conductive substrate may be used to smoothly supply hydrogen gas or oxygen gas to the first gas diffusion layer 40 and the second gas diffusion layer 40', respectively. Representative examples thereof include, but are not limited to, carbon paper, carbon cloth, carbon felt, or metal cloth (referring to a porous film made of metal cloth in a fibrous state or a cloth made of polymeric fiber on which a metal film is formed).

[0033] In addition, it is preferable that the first gas diffusion layer 40 and the second gas diffusion layer 40' are made of a fluorine-based resin that is water-repellent, since this can prevent the efficiency of reactant diffusion from decreasing due to water generated during the operation of the fuel cell. The fluorine-based resin may be polytetrafluoroethylene, polyvinylidene fluoride, polyhexafluoropropylene, polyperfluoroalkylvinylether, polyperfluorosulfonylfluoridealkoxyvinylether, fluorinated ethylene propylene, polychlorotrifluoroethylene, or copolymers thereof. Another embodiment of the present invention relates to a method for manufacturing a membrane-electrode assembly, comprising the steps of directly coating at least one surface of a polymer electrolyte membrane with the coating composition, and drying the polymer electrolyte membrane coated with the coating composition. The step of drying the polymer electrolyte membrane coated with the coating composition may correspond to a step of drying at 50 to 120° C. for 10 to 300 seconds. If the temperature of the drying step is below the above range or the drying time is below the above range, a sufficiently dried catalyst layer may not be formed, and if the drying temperature or the drying time exceeds the above range, the process time may be unnecessarily long and cracks may occur in the catalyst layer. FIG. 4 is a schematic diagram illustrating how a second complex homogeneously dispersed in a coating composition precipitates at the interface between a polymer electrolyte membrane and a catalyst layer in a method for manufacturing a membrane-electrode assembly according to one embodiment of the present invention.

[0034] Referring to FIG. 4, the polymer electrolyte membrane coated with the coating composition is dried, whereby the second complex is precipitated on the polymer electrolyte membrane, forming an ionomer-rich layer. The step of drying the polymer electrolyte membrane may be carried out using various drying methods such as hot air drying, vacuum drying, infrared drying, etc. The temperature and time for drying may be appropriately adjusted depending on the boiling point of the solvent used. Yet another embodiment of the present invention relates to a fuel cell including the membrane-electrode assembly described above. FIG. 5 is a schematic diagram for explaining a fuel cell according to an embodiment of the present invention. Referring to FIG. 5, a fuel cell 200 according to the present invention may include a fuel supply unit 210 that supplies a mixed fuel obtained by mixing fuel and water, a reforming unit 220 that reforms the mixed fuel to generate a reformed gas including hydrogen gas, a stack 230 in which the reformed gas including hydrogen gas supplied from the reforming unit 220 undergoes an electrochemical reaction with an oxidant to generate electrical energy, and an oxidant supply unit 240 that supplies an oxidant to the reforming unit 220 and the stack 230. The stack 230 may include a plurality of unit cells that generate electrical energy by inducing an oxidation / reduction reaction between the reformed gas including hydrogen gas supplied from the reformer 220 and an oxidant supplied from the oxidant supplying unit 240.

[0035] Each unit cell means a unit cell that generates electricity, and may include the membrane-electrode assembly that oxidizes / reduces oxygen in a reformed gas containing hydrogen gas and an oxidant, and a separator plate (also called a bipolar plate, hereinafter referred to as "separator plate") for supplying the reformed gas containing hydrogen gas and the oxidant to the membrane-electrode assembly. The separator plates are disposed on both sides of the membrane-electrode assembly with the membrane-electrode assembly at the center. In this case, the separator plates located at the outermost positions of the stack may be specially referred to as end plates. Of the separation plates, the end plate may be provided with a pipe-shaped first supply pipe 231 for injecting the reformed gas containing hydrogen gas supplied from the reforming section 220 and a pipe-shaped second supply pipe 232 for injecting oxygen gas, and the other end plate may be provided with a first exhaust pipe 233 for discharging the reformed gas containing hydrogen gas that is ultimately left unreacted in the multiple unit cells to the outside, and a second exhaust pipe 234 for discharging the oxidant that is ultimately left unreacted in the unit cells to the outside. In the fuel cell, the separator, the fuel supply section, and the oxidant supply section constituting the electricity generating section are the same as those used in ordinary fuel cells, and therefore detailed description thereof will be omitted in this specification. Hereinafter, the embodiments of the present invention will be described in detail so that a person having ordinary skill in the art to which the present invention belongs can easily carry out the embodiments. However, this is merely an example, and the scope of the present invention is not limited to the following contents.

[0036] [ Manufacturing example: Manufacturing of membrane-electrode assemblies ] Membrane-electrode assemblies according to the following comparative examples and examples were produced. <Comparative Example 1> 10 g of Tanaka's commercial Pt / C catalyst was placed in a reaction vessel and soaked in 50 g of water to prepare a catalyst mixture solution. 40 g of an amorphous first ionomer solution (10 wt%, equivalent weight 725 g / eq) was placed in the reaction vessel and dispersed using a high-pressure disperser to prepare a first homogeneous mixture. A coating composition containing the first homogeneous mixture was directly coated on one side of a polymer electrolyte membrane to prepare a membrane-electrode assembly. <Example 1> 9g of Tanaka's commercial Pt / C catalyst was placed in a reaction vessel and soaked in 200g of water to prepare a synthetic catalyst solution. 30g of amorphous first ionomer solution (10wt%, PFSA; equivalent weight 725g / eq) was placed in the reaction vessel and dispersed using a high-pressure disperser to prepare a first homogeneous mixture. The first homogeneous mixture was dried at 80°C for 8 hours and then heat-treated at 120°C for 2 hours. A second homogeneous mixture containing 1g of h-BN (hexagonal boron nitride) and 10g of a second ionomer solution (10wt%, S-PEEK; equivalent weight 725g / eq) was added to the heat-treated first homogeneous mixture and dispersed using a high-pressure disperser to prepare a coating composition. The coating composition was directly coated on one side of the polymer electrolyte membrane to prepare a membrane-electrode assembly. <Example 2> A membrane-electrode assembly was prepared in the same manner as in Example 1, except that the equivalent weight of the first ionomer was 725 g / eq and the equivalent weight of the second ionomer was 800 g / eq.

[0037] <Example 3> A membrane-electrode assembly was prepared in the same manner as in Example 1, except that 1 g of metal particles having a core-shell morphology, Cu@Ag (Cu core-Ag shell), instead of h-BN, was mixed with the second ionomer solution. <Example 4> A membrane-electrode assembly was prepared in the same manner as in Example 1, except that 1 g of multi-walled carbon nanotubes (MWCNTs) was mixed with the second ionomer solution instead of h-BN. [ Experimental example 1: Chemical durability evaluation ] The chemical durability of Comparative Example 1, Example 1, and Example 2 was evaluated based on the durability evaluation protocol (90°C, 30% RH, 50 kPa, An=H2 / Ca=Air) of the United States Department of Energy (DOE). Specifically, to evaluate the chemical durability of the membrane-electrode assemblies, the OCV hold method was performed for 500 hours, and then the voltage loss was measured, and the measured values ​​are shown in Table 1 below.

[0038] [Table 1] As shown in Table 1, the membrane-electrode assemblies according to Examples 1 and 2 satisfy the DOE standard (voltage loss ≦20%@500hr) and show less voltage loss and chemical durability than the membrane-electrode assembly according to Comparative Example 1. From the above evaluation results, the membrane-electrode assemblies according to Examples 1 and 2 have improved chemical durability compared to Comparative Example 1. [ Experimental example 2: TEM image of an electrode using h-BN as a heat dissipation material ] FIG. 6 is a transmission electron microscope (TEM) photograph of the electrodes of the membrane-electrode assembly according to Example 1. Referring to FIG. 6, it can be seen that the second composite (a composite including the second ionomer and h-BN) is distributed around the first composite. [ Experimental Example 3: TEM image of the second composite for metal particles with core-shell morphology ] FIG. 7 is a transmission electron microscope (TEM) photograph of the second composite body according to Example 3. Referring to FIG. 7, it can be seen that the second composite (a composite including the second ionomer and metal particles having a core-shell shape) is distributed within the second homogeneous mixture.

[0039] [ Experimental Example 4: SEM photo of an electrode using CNT as a heat dissipation material ] FIG. 8 is a scanning electron microscope (SEM) photograph of the electrodes of the membrane-electrode assembly according to Example 4. Referring to FIG. 8, it can be seen that the second composite (the composite including the second ionomer and the carbon nanotubes) is randomly distributed at the interface between the polymer electrolyte membrane and the catalyst layer (or electrode). [ Experimental Example 5: Experiment to prove the critical significance of the content of heat dissipating material ] FIG. 9 is a scanning electron microscope (SEM) photograph of an electrode in which h-BN (hexagonal boron nitride) is 52 wt % based on the total weight of the second homogeneous mixture. Referring to FIG. 9, when the content of h-BN exceeds 50 wt % based on the total weight of the second homogeneous mixture, the h-BN clumps together, and the second ionomer (or free ionomer) is unable to increase the interfacial bonding strength between the polymer electrolyte membrane and the catalyst layer. [ Experimental Example 6: SEM photo of the first segment (or ionomer-rich layer) ] FIG. 10 is a scanning electron microscope (SEM) photograph showing second complexes randomly distributed at the interface (or first segment) between a fuel cell catalyst layer and a polymer electrolyte membrane according to one embodiment of the present invention. Referring to FIG. 10, it can be seen that the second complexes in the first segment (or the third segment) form ionomer-rich layers randomly arranged on both sides of the polymer electrolyte membrane.

[0040] Although the preferred embodiments of the present invention have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements made by those skilled in the art using the basic concept of the present invention defined in the following claims also belong to the scope of the present invention.

Claims

1. A catalyst layer for a fuel cell comprising a first composite and a second composite, The first complex is A carrier; A catalyst including metal particles supported on the support; a first ionomer coated on the surface of the catalyst; Including, The second complex is Heat dissipating materials (excluding particles made of carbon), A second ionomer; and Including, the second ionomer is not coated on the surface of the catalyst; The first ionomer and the second ionomer are the same or different from each other, The heat dissipation material is a catalyst layer for a fuel cell that efficiently dissipates heat generated inside the membrane-electrode assembly during operation of the fuel cell.

2. The first ionomer and the second ionomer are different from each other; The catalyst layer for a fuel cell according to claim 1 .

3. the equivalent weight of the first ionomer and the equivalent weight of the second ionomer are each independently 600 to 1100 g / eq; The equivalent weight of the first ionomer and the equivalent weight of the second ionomer are different from each other; The catalyst layer for a fuel cell according to claim 2 .

4. One of the first ionomer and the second ionomer is a fluorine-based ionomer, and the other is a hydrocarbon-based ionomer. The catalyst layer for a fuel cell according to claim 2 .

5. the first ionomer is a first hydrocarbon-based ionomer; The second ionomer is a second hydrocarbon-based ionomer different from the first hydrocarbon-based ionomer. The catalyst layer for a fuel cell according to claim 2 .

6. the first ionomer is a first fluorine-based ionomer; The second ionomer is a second fluorine-based ionomer different from the first fluorine-based ionomer; The catalyst layer for a fuel cell according to claim 2 .

7. The heat dissipation material is A member selected from the group consisting of metal nanoparticles, ceramic nanoparticles, ultra-high molecular weight polyethylene, polyacetylene, and combinations thereof; The catalyst layer for a fuel cell according to claim 1 .

8. The carrier is 2. The catalyst layer for a fuel cell according to claim 1, which is one selected from the group consisting of carbon-based supports, porous inorganic oxides, zeolites, and combinations thereof.

9. The metal particles are A member selected from the group consisting of platinum, platinum-based alloys, non-platinum-based metals, and non-platinum-based alloys; The catalyst layer for a fuel cell according to claim 1 .

10. The fuel cell catalyst layer according to claim 1 , further comprising a functional additive.

11. The functional additive is At least one selected from the group consisting of radical scavengers, gas barrier particles, hydrophilic inorganic additives, oxygen evolution reaction (OER) catalysts, and combinations thereof; The catalyst layer for a fuel cell according to claim 10.

12. A method for producing a catalyst layer for a fuel cell according to claim 1, comprising the steps of: (S1) homogeneously mixing a first ionomer solution and an aqueous solution in which a catalyst is dispersed, and dispersing them to prepare a first homogeneous mixture; and (S2) adding a second homogeneous mixture obtained by mixing a heat dissipating material and a second ionomer solution to the first homogeneous mixture and dispersing them to prepare a coating composition; A method for producing a catalyst layer for a fuel cell.

13. Between the steps (S1) and (S2), the step of drying the first homogenous mixture at 80 to 100° C. for 8 to 10 hours, and then heat-treating the dried first homogenous mixture at 100 to 120° C. for 2 to 4 hours; The method for producing a catalyst layer for a fuel cell according to claim 12.

14. The heat dissipation material is included in an amount of 1 to 51 wt % based on the total weight of the second homogeneous mixture. The method for producing a catalyst layer for a fuel cell according to claim 12.

15. A polymer electrolyte membrane; and a catalyst layer for a fuel cell according to claim 1 disposed on at least one surface of the polymer electrolyte membrane. Membrane-electrode assembly.

16. The fuel cell catalyst layer comprises: A first segment in contact with the polymer electrolyte membrane; a second segment disposed on the first segment; Including, The membrane-electrode assembly according to claim 15.

17. the second segment does not include the second complex; The content of the second complex per unit volume of the second segment is less than the content of the second complex per unit volume of the first segment. The membrane-electrode assembly according to claim 16.

18. the thickness of the first segment is between 10 and 800 nm (nanometers); The thickness of the second segment is 0.5 to 20 μm (micrometers); The membrane-electrode assembly according to claim 16.

19. A method for producing the membrane-electrode assembly of claim 15, comprising the steps of: directly coating at least one surface of a polymer electrolyte membrane with a coating composition; and drying the polymer electrolyte membrane coated with the coating composition. The method for producing the coating composition comprises: (S1) homogeneously mixing a first ionomer solution and an aqueous solution having a catalyst dispersed therein, and dispersing them to prepare a first homogeneous mixture; and (S2) adding a second homogeneous mixture containing a heat dissipation material and a second ionomer solution to the first homogeneous mixture and dispersing them; A method for producing a membrane-electrode assembly.

20. A fuel cell comprising a membrane-electrode assembly according to any one of claims 15 to 18.

Citation Information

Patent Citations

  • Electrode for fuel cell, membrane-electrode assembly including it, and fuel cell system including it

    JP2008123985A

  • Composition of nanometal particles

    JP2010534562A

  • Colloidal dispersions containing noble metal particles and acidic ionomer components, and methods for their production and use

    JP2016505193A

  • Catalyst layer and electrolyte membrane-electrode assembly for fuel cell, and fuel cell

    JP2019040705A

  • Electrode catalyst-containing dispersion composition and article made therefrom

    JP2020522846A